Pemberdayaan Kesadaran Hak dan Perlindungan PMI di Korea Selatan Berbantuan Buku Saku Berbasis Ilustrasi dan Infografis Diikuti Amazing Together Activity - Yani, Muhamad Turhan; Hidayah, Isti; Riyanto, R Benny; Wiyanto, Wiyanto; Wiriawan, Oce; Wijaya, Andhega (LPPM UMRI, 2025)
Empowerment for Indonesian Migrant Workers (PMI) in South Korea can be focused on protection during their employment. PMIs in South Korea have access to a fairly well-established legal system, but many have not been able to make optimal use of it due to a lack of understanding, language barriers, and limited support. Through empowerment in legal protection, the rights of PMIs can be better safeguarded. In addition, local communities play a vital role in creating a fair and safe working environment for PMIs. The target partners of this community service activity, a collaboration among Indonesian Teacher Education Institutes (LPTK), are groups of PMIs located in Daejeon City, South Korea. The activities took place at Annoor Mosque in Daejeon. The objectives of this community service initiative are to:(1) strengthen understanding and awareness of PMI rights, such as minimum wage, working hours, and holidays;(2) enhance protection for PMIs in South Korea; (3) reinforce solidarity between PMIs, the service team, and the targeted PMI partners. The outcomes of the activities have met the targets, which include: (1) positive responses from the target partners regarding the materials and activities conducted; (2) issuance of a copyright certificate; (3) media publication; and (4) an Implementation Agreement.